(untitled) (Педагогіка вищої та середньої школи, 2022)
The article deals with the peculiarities of bringing up of shulcnts which are taught in the reserve officers’ program. The author takes into consideration the modern demands of criteriavi lation and definition o f improving bringing up methods which provide its efficiency at the higher education establishment chair.